(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Outcome of acute limb ischaemia (ALI) is depends on the timely intervention. Delayed reperfusion of acute occlusive limb ischemia causes local and systemic serious consequences and is the main cause of morbidity and mortality in these patients. Objective: To identify the factors impeding the management and outcome of ALI in a tertiary level hospital. Materials and Methods: This cross sectional study evaluated reporting time and management of 42 patients with ALI between Jan 2016 to Jan 2018 in Combined Military Hospital Dhaka. Late presentation of ALI is defined as reporting of patient after 72 hours of symptoms. Time of presentation, Grades of ischemia, co-morbidities, morbidities and mortality were recorded. Results: During the study period, 42 patients were included, 25 female (59.5%) and 17 male (40.5%). Average age was 63 years (30 years – 87 years). 38 (90%) patients with lower limb ischaemia and 4 (10%) patients with upper limb ischaemia. 2 patients (4.7%) reported within 6 hours of symptom, 6 patients (14.3%) presented within 24 hours, 11 patients (26.3%) within 72 hours and 23 patients (54.7%) after 72 hours. On admission, 16 patients had grade III ischemia, 18 had grade IIb, 8 had grade IIa. 12 patients died (28.5%) and 19 (45%) patients had amputation. The risk factors of amputation were grade of ischemia, extremity (lower limb 45% vs. Upper limb 0%), age and co-morbidity. Conclusion: Late presentation of acute occlusive ischemia carries high morbidity and mortality. Lack of awareness and Negligence of symptoms delay the reporting time to hospital. Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 59-61